Effect of adding Eruca Sativa Seeds and Vit.E.on the diet of mal Awassi lambs on same production traits: Manhal Habib Salman Al-Fityin ;Mudhaffer Nafic ALSaig - Al-Fityin, Manhal Habib Salman (The Iraqi Journal of Veterinary Medicine, 2009)
The aim of this study was to find out the effect of adding Eruca Sativa seed in concentrate diet alone orwith Vit.E administration on productivity of male Awassi lambs.This study was conducted onVeterinary College,Baghdad University.Fifteen Awassi ram lambs at age of 5-6 months ,were dividedequally in to three groups accordingly and treated as followed :The frist group A(G)was fed onconcentrate diet containing Eruca Sativa seeds (5%)at a rate of 400g/day /haed,The second groupB(G+E) was fed on the same ration mentioned above with Vit.E with a dose of 400mg/head was givenorally bimonthly ,The animals in the third group C (control)were fed on a concentrate diet free ofEruca Sativa at a rate of 400g/day.All animals offered 0.5kg alfalfa/day/head and freely grazing for 3-6h daily. The results revealed the followings:Body weight was increased in all animal progressively.Animals in group (G)and (G+E)were significantly (p<0.05) or mathematically increased comparedwith the control groups especially in late perieds.The absolute gains of the first and second groups weresignificantly (p<0.05) higher than the control group .Body skeletal measurements of all animalsincreased progressively .The first and second groups showed better values as compared with the controlgroup.Testes measurements progressively increased with age for all animals .Testes circumferencesrecorded significantly (p<0.05) hiyher in group G and G+E at the end period of the experimentcompared with the control group.By using Eruca Sativa seeds caused an improvement in wool yieldand its traits viz.;greasy and clean wool,staple length and fiber length and diameter.However,thesecond group recorded better values in some productivity traits such as body weight and woolproduction compared with the first group.There fore ,it was concluded that adding Eruca Sativa seeds in concentrate diet caused an improvementin productivity traits. Vit.E.administration with Eruca Sativa seeds caused more improvement in someproductive traits.